STRENGTH AND CRACK RESISTANCE OF BASALT FIBER-STRENGTHENED REINFORCED CONCRETE BEAMS WITH COMPOSITE REINFORCEMENT: A COMPARATIVE ANALYSIS BASED ON EUROCODE 2 - Muxtorova , Shahzoda; Nazirov , Ayubxon (INTERNATIONAL MULTIDISCIPLINARY SCIENCE CONFERENCE, 2026)
This paper presents a theoretical analysis of the strength and crack resistance of flexural reinforced concrete beams reinforced with composite FRP bars and strengthened by basalt fibers. Although FRP reinforcement provides high tensile strength and excellent corrosion resistance, its relatively low modulus of elasticity compared to steel reinforcement leads to increased deflections and crack widths, which is considered a key serviceability limitation. The incorporation of basalt fibers into concrete is examined as an effective method to improve crack resistance by acting as micro-reinforcement, bridging microcracks and limiting crack propagation. Furthermore, the Eurocode 2 crack width calculation approach is reviewed and compared with the structural behavior of FRP reinforced concrete members. Based on the reviewed literature, the combined use of basalt fibers and FRP reinforcement is identified as a promising solution for enhancing serviceability performance, durability, and long-term reliability of reinforced concrete beams in aggressive environments.